2004
DOI: 10.1603/0022-0493-97.4.1465
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aeration and Spinosad for Suppressing Insects in Stored Wheat

Abstract: Field studies were conducted from July 2002 to January 2003 for evaluating the effects of controlled aeration and a commercial biological insecticide, spinosad, in suppressing insect populations in stored wheat. Six cylindrical steel bins were filled with newly harvested (2002 crop year) hard red winter wheat on 9 and 10 July 2002. Each bin contained 30.7 metric tons (1,100 bu) of wheat. Wheat in two bins was left untreated (control), whereas wheat in two bins was treated with spinosad, and in another two bins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
4
20
0
5
Order By: Relevance
“…ml À1 solution resulted in a spinosad residue deposit nearly eight times higher than the tolerance level of 1.5 mg (a.i) kg À1 of grain. In real world situations, uniform coating of kernels with insecticide is rare and uneven distribution of insecticide on kernels and uneven distribution of treated kernels in a grain lot are very common (Flinn et al, 2004;Subramanyam et al, 2007). When grain is treated with an insecticide as it is being augured into the storage bins, not all kernels are treated uniformly and some kernels are not treated at all, and this may result in percentage of treated and untreated kernels to range anywhere between 10 and 100.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations
“…ml À1 solution resulted in a spinosad residue deposit nearly eight times higher than the tolerance level of 1.5 mg (a.i) kg À1 of grain. In real world situations, uniform coating of kernels with insecticide is rare and uneven distribution of insecticide on kernels and uneven distribution of treated kernels in a grain lot are very common (Flinn et al, 2004;Subramanyam et al, 2007). When grain is treated with an insecticide as it is being augured into the storage bins, not all kernels are treated uniformly and some kernels are not treated at all, and this may result in percentage of treated and untreated kernels to range anywhere between 10 and 100.…”
Section: Tablementioning
confidence: 99%
“…kg À1 , on an average, resulted in residue deposition of only 75% of the actual rates applied (Fang et al, 2002b). In 4.72 m diameter and 3.35 m high round steel bins holding 30.7 metric tons of 10.8% moisture wheat, Flinn et al (2004) reported that spinosad deposition soon after treatment at 1 mg (a.i.) kg À1 ranged from 0.40 to 0.88 mg (a.i.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial metabolites have insecticidal properties in it (Mertz & Yao 1990). Spinosad retains its insecticidal activity in stored grains from six months to one year Flinn et al 2004). It is an excellent grain protectant because its efficacy is not disrupted by grain moisture (Fang & Subramanyam 2003).…”
Section: Use Of Insecticidesmentioning
confidence: 99%